We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
658
1
avatar+644 

Find the center of -4x^2 + y^2 - 2y = 3.

 Nov 20, 2017
 #1
avatar+99592 
+2

-4x^2 + y^2 - 2y  = 3

 

Rewrite as

 

y^2 -2y  - 4x^2  = 3     comlplete the square on y

 

y^2 - 2y + 1  -  4x^2  =  4       factor the frst three terms

 

(y - 1)^2   - 4x^2  = 4       divide through by 4

 

(y - 1)^2      -   x^2              

_______        ____         =      1

    4                  1

 

This is a "vertical" hyperbola.....the center is   (0, 1)

 

 

cool cool cool

 Nov 20, 2017

37 Online Users

avatar
avatar
avatar